DIGITAL SUPPLY CHAIN TECHNOLOGY MANAGEMENT USING THE EXAMPLE OF DDEX, DOTBC AND OMI - R. Veynberg; O. Litvishko (Вестник Северо-Кавказского федерального университета)
The modern multilevel nature and accessibility of user content makes it difficult to get complete and reliable information about it. This is why companies need to standardize the flow of incoming information in order to simplify its analysis and interpretation. Effective functioning of both the logistics system and the entire supply chain is impossible without the introduction of integrated digital technologies that provide end-to-end process management and provide flexibility, reliability and transparency of the supply chain for all network contractors, which is important for maintaining the company’s competitiveness. Digitalization is the main driver of the development of all supply chains. it allows us to ensure their protection and reliability, as well as legal confirmation of any actions of contractors.